Exocrine Pancreatic Maturation in Pre-term and Term Piglets Supplemented With Bovine Colostrum - Arévalo Sureda, Ester; Pierzynowska, Kateryna; Weström, Björn; Sangild, Per Torp; Thymann, Thomas (Frontiers in Nutrition, 2021)
Preterm infants have an immature digestive system predisposing to short- and long-term complications including feeding intolerance, maldigestion and necrotizing enterocolitis (NEC). Optimal feeding strategies are required to promote maturation of the gut including the exocrine pancreas. Little is known about age- and diet-related development of pancreatic exocrine enzymes following preterm birth. Currently, bovine colostrum supplementation is investigated in clinical trials on preterm infants. Using pigs as models for infants, we hypothesized that pancreatic enzyme content is 1) immature following preterm birth, 2) stimulated by early colostrum supplementation, and 3) stimulated by later colostrum fortification. Thus, using piglets at models for infants, we measured trypsin, amylase, lipase and total protein in pancreatic tissue collected from piglets delivered by caesarean section either preterm (90% gestation) or close to term. Experiment1: Preterm and term pigs were compared at birth and 11 days. Experiment2: Preterm and term pigs were either enterally supplemented with bovine colostrum or fed total parenteral nutrition for five days, followed by exclusive milk feeding until day 26. Experiment3: Preterm pigs were fed bovine´s milk with or without colostrum fortification until 19 days. The results showed that pancreatic trypsin, amylase and total protein contents were reduced in preterm vs. term pigs. Trypsin mainly increased with advancing postconceptional age (2-fold), while amylase was affected predominantly by advancing postnatal age, and mostly in preterm pigs from birth to 11 or 26 days. Colostrum feeding in both term and preterm piglets decreased trypsin and increased amylase contents. Lipase activity decreased with advancing gestational age at birth and postnatal age, with no consistent responses to colostrum feeding, with lipase activities decreasing relative to total pancreatic protein content. In summary, key pancreatic enzymes, amylase and trypsin, are immature following preterm birth, potentially contributing to reduced digestive capacity in preterm neonates. Rapid postnatal increases occurs within few weeks of preterm birth, partly stimulated by enteral colostrum intake, reflecting a marked adaptation capacity. Alternatively, lipase is less affected by pre-/postnatal age and feeding. Thus, there is a highly enzyme-specific and asymmetric perinatal development of the exocrine pancreas.